Level of Including Values in Arabic Language Course for 3 G Primary, in the Kingdom of Saudi Arabia, in Light of the Cross-Cutting Dimensions of the Public Education Curricula Standards - Al-Rasasimah, Taghreed Saeed; Al-Arfaj, Abeer Mohammed (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to identify the level of including indicators of values in Arabic Language course assigned for 3rd primary grade in the light of cross-cutting dimensions of public education curricula standards in KSA. To achieve this objective, a descriptive methodology, represented in content analysis, was used. An analysis sheet was designed from a number of values that were approved by the Education and Training Evaluation Authority in the light of cross-cutting dimensions of public education curricula standards. The final analysis sheet was composed of 28 indicators applied on Arabic Language course assigned for the 3rd primary grade in KSA in semesters I and II, version of the year 1443 (AH)- 2021. The data were then analyzed through calculating frequencies. Accordingly, the study revealed that: the level of including the indicators of values in the sample course ranged between average and low as follows: Responsibility scored the top rank (level of inclusion = average; P = 38.58%) while the level of inclusion of the other indicators was low: Self-esteem scored the 2nd rank (P = 21.78%); Cognitive Passion scored the 3rd rank (P = 18.58%) ; Moderation scored the 4th rank (P = 11.48%); Fear of Allah scored the 5th rank (P = 6.04%); Work Estimation and Mastering scored the 6th rank (P = 3.55%). The overall level of including values in the sample course was average (55.85%). Based on the findings of the study, a number of recommendations were introduced notably: considering the logical balance when including values in the subject of "Loghati" of the 3rd primary class in KSA in the light of joint dimensions of public education curricula criteria.